Codificação de canal para redes 5G utilizando códigos polares - Martão, Vanessa Beatriz [UNESP] (2018)
Polar codes are linear block codes with low computational cost that have great potential to be used in 5G technology, due to evidence that it achieves the Shannon's channel capacity. These codes are essentially binary, being implemented in symmetric and memoryless channels. The objective of this work was study the coding and decoding strategy of the polar codes for the application in the 5G networks. To this end, we have introduced the elements of information theory and coding. After that we did a study about the channel polarization technique that separates the good channels from the bad ones. We studied coding and decoding strategies for codes, and a computational implementation to verify its efficiency. The results showed that the larger the N size of the codeword, the closer the signal is to the limit of the Shannon's channel capacity theorem